THE INFLUENCE OF ORGANIZATIONAL CULTURE, MOTIVATION, AND LECTURER CERTIFICATION ON LECTURER PERFORMANCE (CASE STUDY AT ALMUSLIM UNIVERSITY) - Yanna, Sri; Yusuf, M (JURNAL KEBANGSAAN, 2020)
The purpose of this study was to determine and measure 1) The influence of organizational culture on Lecturer Performance at Almuslim University. 2) The influence of motivation on Lecturer Performance at Almuslim University. And 3) The effect of lecturer certification on the Performance of Lecturers at Almuslim University. This research was conducted at the University of Almuslim Peusangan Bireuen. As for the variables of this study are organizational culture, lecturer work motivation, lecturer certification, and lecturer performance. The study was conducted on 76 lecturers who are qualified Serdos, in 7 (seven) faculties at the University of Almuslim in August - September 2019 .. The results showed that the level of organizational culture according to the lecturer had reached 80.82 percent in supporting lecturer performance, while the level of motivation lecturer work has reached 81.51 percent. The average level of lecturer performance reaches good qualifications. The results of the path analysis, with a 95 percent confidence level, found that, 1). There is a causal relationship between organizational culture and lecturer work motivation which is very significant, as well as work motivation with lecturer certification, so as to ensure that between independent variables (exogenous) a causal relationship occurs, 2). There is an influence of organizational culture both directly and indirectly on the performance of lecturers by 30.99 percent. 3). There is a direct and indirect influence on the aspects of lecturer work motivation on the lecturer performance level of 29.87 percent. 4). While the effect of the aspect of granting lecturer Certification to lecturer performance is quite significant at 11.40 percent. 5). The magnitude of the contribution of organizational culture factors, work motivation of lecturers and lecturer certification on the performance of lecturers amounted to 74.4 percent. Keywords: Organizational culture, Lecturer work motivation, Lecturer certification, Lecturer performance